2019
DOI: 10.12688/f1000research.19571.2
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan of cleft lip triads identifies parent-of-origin interaction effects between ANK3 and maternal smoking, and between ARHGEF10 and alcohol consumption

Abstract: Background: Although both genetic and environmental factors have been reported to influence the risk of isolated cleft lip with or without cleft palate (CL/P), the exact mechanisms behind CL/P are still largely unaccounted for. We recently developed new methods to identify parent-of-origin (PoO) interactions with environmental exposures (PoOxE) and now apply them to data from a genome-wide association study (GWAS) of families with children born with isolated CL/P. Methods: Genotypes from 1594 complete triads a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
0
10
0
3
Order By: Relevance
“…Another candidate at 9p21.3 is FOCAD , located ~350Kb downstream of the peak SNP, which is a potential tumor suppressor highly expressed in brain tissues. Haaland et al identified a parent-of-origin interaction effect between FOCAD and maternal smoking contributing to cleft lip [ 37 ]. In order to determine the possible roles of genes at this locus on facial traits, subsequent functional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate at 9p21.3 is FOCAD , located ~350Kb downstream of the peak SNP, which is a potential tumor suppressor highly expressed in brain tissues. Haaland et al identified a parent-of-origin interaction effect between FOCAD and maternal smoking contributing to cleft lip [ 37 ]. In order to determine the possible roles of genes at this locus on facial traits, subsequent functional studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…8,39 Analysis methods such as log-linear and multinomial modeling approaches are particularly appealing as they can readily be adapted to accommodate the broad spectrum of various hybrid designs as well as a wide array of causal scenarios and genetic effects. 11,13,17,24,27,29,35,40 As an example, they can easily be extended to include the maternal-fetal genotype incompatibility test. 41 Nevertheless, although the hybrid design combines the merits of both the case-control and case-parent designs, a straightforward combined analysis may still be influenced by population stratification or non-Mendelian transmission.…”
Section: The Hybrid Designmentioning
confidence: 99%
“…For example, maternal exposures such as alcohol consumption, smoking, or vitamin intake during the periconceptional period might modify the association between SNPs and a birth defect. 25,28,29 Interactions between genetic effects and categorical exposure variables are incorporated into the log-linear framework of Haplin by fitting the log-linear model separately for each exposure stratum. A Wald test is then applied to detect whether the relative risk estimates differ significantly across exposure levels.…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following one such GWAS study in European and Asian case-parent trios (Beaty 2010), candidate gene and pathway-based GxE analyses have suggested interactions between smoking and RUNX2 (11), and between multiple exposures and BMP4 (12). Genome-wide GxE using a variety of statistical approaches have identified interactions for maternal smoking, alcohol, or folate supplementation in cleft palate (13-15) and cleft lip with or without cleft palate (16, 17).…”
Section: Introductionmentioning
confidence: 99%